Oral health of Dutch primary school children in relation to social and health aspects - Brenda G. Grift; Denise Duijster; Geert J.M.G. van der Heijden; Josef J.J.M. Bruers; Katarina Jerković-Ćosić (Medical Journals Sweden, 2024)
Objective: This research investigated the oral health status of Dutch primary school children aged 10-12 years in Utrecht and its association with demographic characteristics, lifestyle factors, general psychosocial health, and dental treatment, to guide targeted interventions to improve children's oral and overall well-being. Materials and methods: A cross-sectional survey was conducted at 49 primary schools in Utrecht in 2017 and 42 schools in 2019. The questionnaire covered background characteristics (7 questions), psychosocial health (14 questions), nutrition and exercise (20 questions), school and leisure time (26 questions), home situation (23 questions), and oral health (4 questions). Associations were analyzed using multivariate logistic regression. Results: Data from 5,426 children were analyzed. Prior to the survey, 11% did not visit a dentist, 23% had a toothache, 22% had a cavity filled, and 8% had a tooth extracted. Independent predictors for increased odds of oral health problems were migration background, poor general health, drinking more than two glasses of soft drinks per day, having ever drunk alcohol, having fear of failure, experiencing problems at home and/or coming from average or low socioeconomic position group. Factors associated with increased odds of dental treatment, such as cavity filled and tooth extracted, were migration background, fear of failure and home problems. Conclusions: These findings emphasize the need for targeted prevention to improve the oral health of children with a migration background, average or low socioeconomic position and/or with poorer general and psychosocial health, unhealthy diets and problems in the home situation, within a community-based and transdisciplinary approach.